The Construction of Interactive Classrooms in Colleges and Universities Based on Big Data Analysis and Benchmark Graph Neural Network. (12th May 2022) - Shen, Peipei
Abstract : In the 21st century, big data technology is bringing unprecedented changes to all walks of life. In the era of big data, new technologies, new models, and education and teaching practices are constantly looking for the best combination. Words such as interactive classroom and teaching informatization are undergoing a process of continuous enrichment of their own content with the update of new technologies and the realization of various applications. The methods of online teaching are merging with the conventional teaching practice of universities. Interactive classroom is the representative of combining the advantages of webcasting technology with classroom teaching. It uses video and audio acquisition and coding technology, C4.5 algorithm, to calculate and transmit data and analyzes information entropy-related concepts, etc., to transmit interactive classroom teaching to various spaces. This has increased students' interest in learning by nearly 50%, and teachers' evaluation scores for students have also increased to nearly twice, which shows the impact of interactive classrooms on students' self-drive. The key to the classroom does not refer to long distances, to break time and space, or to the expansion of learning groups and the unlimited sharing of educational resources. It should be the learner's self-cognition and the barrier-free interaction with the teacher, which have been reflected in the interactive classroom.